BIOMASSA PURUN TIKUS (Eleocharis dulcis Trin.) PADA TIGA TITIK SAMPLING DI DESA PUNTIK KECAMATAN ALALAK KABUPATEN BARITO KUALA - Atika Setyorini; Krisdianto Krisdianto; Syaiful Asikin (Bioscientiae, 2009)
Biomass of Purun Tikus (Eleocharis dulcis. Trin) in Three Sampling Locations in Desa Puntik Kecamatan Alalak Kabupaten Barito Kuala South Kalimantan (By: Atika Setyorini; Advisors: Krisdianto, Syaiful Asikin, 2009; 41 pages) This research is aimed to know the biomass of purun tikus in three samplings Desa Puntik Kecamatan Alalak Kabupaten Barito Kuala. The taking of plant sample, soil and water in three location there are Desa Puntik Luar, Puntik Tengah and Puntik Dalam by making the plote size 1x1 m2 in each location. The purun tikus sample on each plot is taking for three times then composited the sample. The parameter that measured such as the plant high, dry weight, wet weight, water rate and rough fibre of purun tikus every two weeks for six weeks observation time. Beside that also analyze the contain of N, P, K in soil. The highest rate of wet weight biomass is 8.354,78 gr/m2 and dry weight biomass is 3.282,68 gr/m2, and the highest rate of high plant is 31,72 cm, the number of individu in each clump is 16, dry weight is 1,13 gr, wet weight is 1,84 gr, water rate is 83,16% and the rough fibre is 10,75%.